Succinic semialdehyde dehydrogenase deficiency (SSADHD): Pathophysiological complexity and multifactorial trait associations in a rare monogenic disorder of GABA metabolism. (October 2016) - Malaspina, P.; Roullet, J.-B.; Pearl, P.L.; Ainslie, G.R.; Vogel, K.R.; Gibson, K.M.
Abstract: Discovered some 35 years ago, succinic semialdehyde dehydrogenase deficiency (SSADHD) represents a rare, autosomal recessively-inherited defect in the second step of the GABA degradative pathway. Some 200 patients have been reported, with broad phenotypic and genotypic heterogeneity. SSADHD represents an unusual neurometabolic disorder in which two neuromodulatory agents, GABA (and the GABA analogue, 4-hydroxybutyrate), accumulate to supraphysiological levels. The unexpected occurrence of epilepsy in several patients is counterintuitive in view of the hyperGABAergic state, in which sedation might be expected. However, the epileptic status of some patients is most likely represented by broader imbalances of GABAergic and glutamatergic neurotransmission. Cumulative research encompassing decades of basic and clinical study of SSADHD reveal a monogenic disease with broad pathophysiological and clinical phenotypes. Numerous metabolic perturbations unmasked in SSADHD include alterations in oxidative stress parameters, dysregulation of autophagy and mitophagy, dysregulation of both inhibitory and excitatory neurotransmitters and gene expression, and unique subsets of SNP alterations of the SSADH gene (so-called ALDH5A1, or aldehyde dehydrogenase 5A1 gene) on the 6p22 chromosomal arm. While seemingly difficult to collate and interpret, these anomalies have continued to open novel pathways for pharmacotherapeutic considerations. Here, we present an update on selected aspects of SSADHD, the ALDH5A1 gene, and future avenues for research on this rare disorder of GABA metabolism. Highlights: Aspects of the current knowledge of the role of the SSADH enzyme are summarized. Pathological and polymorphic variations are responsible for SSADH enzyme variability. Integrated genomics and metabolomic approaches for treatment of SSADHD patients.